Feminisme, Femininitas & budaya popular/Joane Hollows;penerjemah, Bethari Anissa Ismayasari ; editor,Siti Jamilah - Hollows, Joanne; Ismaytasari, Bethari Anissa. Siti Jamilah (2010)
viii, 295 hlm 21 cm